2022
DOI: 10.1021/acscatal.2c01989
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Fe Doping in Tuning the Size and Dispersion of GaN Nanocrystallites for CO2-Assisted Oxidative Dehydrogenation of Propane

Abstract: The Fe-doped silicalite-1 zeolite as a matrix was employed to implant GaN nanocrystallites via a combined wet impregnation with in situ nitridation method. Direct spectroscopic evidences under a vacuum unraveled that the incorporation of the isolated framework Fe atoms could cause the generation of more interior silanols and especially hydrogen-bonded groups of silanol nests, where the solvated Ga3+ ions and urea in an N2 atmosphere at high temperatures were transformed into the highly dispersed GaN nanocrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Introducing Fe 3+ sites in the zeolite framework has been reported to be a reliable way to inhibit the reduction and carbonization of Fe species. Li et al 141 prepared Fe/S-1 catalysts with different Si/Fe ratios via the hydrothermal synthesis method using EDTA as an Fe complexant and studied the catalytic mechanism of Fe in the S-1 framework for CO 2 -OPDH (Fig. 11).…”
Section: Metal Oxide-based Catalystsmentioning
confidence: 99%
“…Introducing Fe 3+ sites in the zeolite framework has been reported to be a reliable way to inhibit the reduction and carbonization of Fe species. Li et al 141 prepared Fe/S-1 catalysts with different Si/Fe ratios via the hydrothermal synthesis method using EDTA as an Fe complexant and studied the catalytic mechanism of Fe in the S-1 framework for CO 2 -OPDH (Fig. 11).…”
Section: Metal Oxide-based Catalystsmentioning
confidence: 99%
“…43 All of these peaks showed lower intensities in the catalysts under vacuum conditions obtained at different temperatures compared with the support. The results indicated that upon GaN introduction, the silanol decreased, indicating that the Si−OH group was reacted with GaN to from Si−O− GaN-H species, 44 but not covered by GaN.…”
Section: Preparation Of the Hns-1 Support And Catalystsmentioning
confidence: 99%
“…402 °C, Figure S40). 59 The greater affinity of CoP@ ZnIn 2 S 4 than pristine ZnIn 2 S 4 for NBI may originate from its much larger specific surface area (233 vs 141 m 2 g −1 for ZnIn 2 S 4 ) that could provide more adsorption sites. 60 Furthermore, by selecting Co in CoP@ZnIn 2 S 4 and Zn in ZnIn 2 S 4 as NBI adsorption sites, DFT calculations in Figure 5a reveal a relatively lower adsorption energy of CoP@ZnIn 2 S 4 (−0.51 eV) than ZnIn 2 S 4 (−0.98 eV).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%